The effect of a new in-hospital trauma care model on the outcomes of severely injured trauma patients in the emergency department: a retrospective observational study in China - Qiu Zhao; Yue Zhao; Tingting Ke; Caili Lin; Yao Xu; Yuanyuan Xu; Shuli Liu; Xinqun Li (BMC Emergency Medicine)
Abstract Background The mortality and disability rates among severely injured trauma patients are very high. This study aimed to investigate whether a new in-hospital trauma care model can improve emergency care efficiency and enhance the prognosis of severely injured trauma patients. Methods This retrospective observational study included 366 severely injured trauma patients (ISS ≥ 16) who were admitted to the emergency department of a tertiary hospital between 2023 and 2024. Based on the emergency care model used, patients were divided into the traditional model group (n = 213) from January to April 2023 and the new model group (n = 153) from January to April 2024. The general clinical data, prognosis information, as well as seven emergency quality control indicators for both groups were collected and analyzed. Results The study included 270 male patients (73.8%) and 96 female patients (26.2%), with a mean age of 56 (44, 69) years. No significant differences were found between the two groups regarding gender, age, time since injury, mechanism of injury, and vital signs upon admission (P > 0.05). The new model group had significantly shorter times for establishing effective circulation access (15.66 ± 3.36 vs. 9.44 ± 3.18 min), establishing an artificial airway (36.90 ± 12.23 vs. 23.91 ± 9.07 min), preparing blood transfusion (48.84 ± 5.73 vs. 31.0 ± 64.67 min), completing whole-body CT scans (57.18 ± 8.26 vs. 42.17 ± 7.28 min), and developing a definitive treatment plan (77.45 ± 6.26 vs. 56.50 ± 6.35 min) compared to the traditional model group. Additionally, the new model group had a significantly higher rate of bedside FAST completion (92.8% vs. 53.1%) and a higher success rate of resuscitation within the first hour (70.9% vs. 85.0%) than the traditional model group. Regarding prognosis, the new model group had a lower overall in-hospital mortality rate (12.1% vs. 5.9%) and a lower incidence of complications such as DIC and ARDS (23.9% vs. 9.2%, all P < 0.05). Conclusion The new in-hospital trauma care model significantly enhanced the in-hospital emergency care efficiency, reduced in-hospital mortality, and decreased the incidence of complications for severely injured patients, which may serve as a useful reference for developing countries in similar settings. Clinical trial number Not applicable.